PERAN LINGKUNGAN KERJA DAN MODAL SOSIAL TERHADAP KETAHANAN GURU DI SEKOLAH DASAR ISLAM: UJI SEM-PLS - Hazawawi, Muhtar; Sutrisno; Ambo' Dalle, Abd. Rahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background of this study is based on the high number of private Islamic Elementary Schools (Madrasah Ibtidaiyah) in Malang, which ranks third in East Java, and the complexity of structural pressures faced by teachers, such as low welfare, excessive administrative burdens, and limited professional certification coverage. The study used a quantitative explanatory approach with a cross-sectional survey method of 56 Islamic elementary school teachers in Malang Regency who were selected purposively. Data analysis was conducted using SEM-PLS to test a structural model involving two exogenous variables (work environment and social capital) and one endogenous variable (teacher resilience). The results of the analysis showed that the work environment had a positive and significant effect on teacher resilience (t = 5.775; p = 0.00), and social capital also had a positive and significant effect on teacher resilience (t = 2.202; p = 0.028). These findings confirm that amid the structural pressures surrounding private madrasah teachers, resilience is not merely a personal attribute, but rather a psychosocial construct that can be strengthened through the creation of a conducive work environment, encompassing both physical and non-physical dimensions, as well as the development of social capital in the form of collective norms, relational networks, and trust among madrasah members. Practically, the results of this study recommend that stakeholders at the Ministry of Religious Affairs and Islamic education foundations design institutional interventions that focus on optimizing work ecology and strengthening social cohesion as non-financial strategies to support teacher resilience and maintain the sustainability of the quality of basic Islamic education.